Hakikat Moderasi Beragama: Eksplorasi Filsafat Pendidikan Islam dan Relevansinya dalam Pendidikan Islam Kontemporer - Abdullah Aziz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The difference in every creature is a blessing from God. Through differences, it is expected to strengthen kinship and togetherness among human beings. Moderation is an attitude of balance, fairness and without discrimination or intervention, thus creating a condition of a fair and harmonious society. Moderation has also been stated in the book of God (Al-Qur'an). It should be noted that moderation must exist in all aspects of human life, whether religious, social, educational, cultural and so on. Indonesia is a country whose society is plural and multicultural. It is not surprising that there are diverse differences. A moderate attitude needs to be instilled to maintain the integrity of relationships both individually, in groups and in the state. Recently, Indonesia has been bombarded with issues about religion, such as blasphemy, hate speech, discrimination of minority communities, extreme groups and others. The purpose of this research is to instill and understand the meaning of the nature of religious moderation and the philosophy of Islamic education as a guide to society, state, and life. Through Islamic education is the right solution to understand the meaning of tolerance, justice, harmony, balance and love of peace. This research uses descriptive qualitative methods with library research studies sourced from books, journals and the Qur'an. The results of the study show that there is a value of tolerance, justice, harmony, balance and love of peace.